TUMBAL KEMENANGAN BARATAYUDA - Triyogo, YB. Rahno (Institut Seni Indonesia Surakarta, 2024)
The issue of tumbal has been known by nations since the ancient times. The types and forms can be in the form of property, animals, or humans of high value. Tumbal is needed in order to achieve a great desire such as building a building, reservoir, bridge, wealth, getting a partner, or achieving a certain position. In the Nusantara tradition, tumbal is often considered synonymous with the word korban (victim), which is interpreted negatively. It is in contrast to tumbal which is considered positive. The word korban is identical to korban persembahan, also with tumbal tawur. The Baratayuda War was a major war that would determine the survival of the Kurawa and Pandawa. To face this major war, both sides prepared themselves both from militaristic as well as spiritual perspectives. From a spiritual perspective, both prepared tumbal tawur which was offered to the supernatural power, the ruler of the universe who would give victory. This article compares the tumbal tawur that would be carried out by the Kurawa and Pandawa. This is important because it is possible that the quality of the tumbal tawur will determine their victory. The strategy used is to compare how to get the tumbal tawur, how to perform tumbal tawur ceremony or korban, the organizer of the korban, and the directed recipient of the korban.